Feasibility study of laser-driven neutron sources for pharmaceutical applications. (13th January 2023) - Mori, Takato; Yogo, Akifumi; Arikawa, Yasunobu; Hayakawa, Takehito; Mirfayzi, Seyed R.; Lan, Zechen; Wei, Tianyun; Abe, Yuki; Nakai, Mitsuo; Mima, Kunioki; Nishimura, Hiroaki; Fujioka, Shinsuke; et al.
Abstract: We predict the production yield of a medical radioisotope ^67 Cu using ^67 Zn(n, p) ^67 Cu and ^68 Zn(n, pn) ^67 Cu reactions with fast neutrons provided from laser-driven neutron sources. The neutrons were generated by the p+ ^9Be and d+ ^9 Be reactions with high-energy ions accelerated by laser–plasma interaction. We evaluated the yield to be (3.3 ± 0.5) × 10 ^5 atoms for ^67 Cu, corresponding to a radioactivity of 1.0 ± 0.2 Bq, for a Zn foil sample with a single laser shot. Using a simulation with this result, we estimated ^67 Cu production with a high-frequency laser. The result suggests that it is possible to generate ^67 Cu with a radioactivity of 270 MBq using a future laser system with a frequency of 10 Hz and 10, 000-s radiation in a hospital.